On the compression behavior of remolded cement-admixed soft clay. Issue 3 (3rd April 2018) - Jiang, Yuzhou; Wang, Dongxing; Di, Shengjie
ABSTRACT: Although extensive research has been performed on the mechanical properties of cement-stabilized clays, quite a few attempts have been made on the compression behavior of remolded cement-admixed clays. The results from oedometer tests have been discussed to investigate the compressibility of remolded cement-admixed clays, taking into consideration cement amount and curing time. The findings show that the difference in shape and position of compression curves is attributed to cement amount and curing time. Most compression index ( C c ) values of remolded cement-admixed clays are greater than those of untreated clay due to the presence of remolded yield stress σ′yr that is closely related to initial water content and clay fabric. Based on the obtained test data, the relationships of C c vs. e 0, C c vs. w 0, C c vs. e 1, C c vs. e yr, and σ′yr vs. e yr are preliminarily discussed and quantitatively established. Especially, an important divergence of void index I v at effective stress σ′v less than remolded yield stress σ′yr can be observed at different cement amounts and curing durations. Being independent on cement amount, curing time, and initial state of soil, an excellent convergence occurs at stress σ′v greater than yield stress σ′yr . The normalized compression curves of I v vs. σ′v at σ′v  > σ′y can be expressed by a unique line that agrees well with intrinsic compression line (ICL) and extended ICL.